2011
DOI: 10.1080/13664530.2011.608513
|View full text |Cite
|
Sign up to set email alerts
|

Classroom teachers’ efficacy in teaching healthy behaviour content

Abstract: This study, grounded in Self-Efficacy Theory, investigated classroom teachers' self-efficacy changes related to teaching healthy behaviour content after participating in ongoing workshops. Participants were 50 male and female teachers at the primary (n = 17) and secondary (n = 33) levels from two schools in one Native American community. Teacher participants completed two previously validated teaching efficacy instruments. Results showed that student healthy behaviour knowledge scores were linearly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…One of the main challenges for pre-service teaching is finding teaching strategies and methodologies that can improve effective, efficient, attractive teaching behaviours and provide students with experience in learning. The success of pre-service teachers has been shown to increase during student teaching, but significantly decreased in the first year of teaching when teachers were in a new context (Hoy & Spero, 2005;Kulinna, Cothran, & Kloeppel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges for pre-service teaching is finding teaching strategies and methodologies that can improve effective, efficient, attractive teaching behaviours and provide students with experience in learning. The success of pre-service teachers has been shown to increase during student teaching, but significantly decreased in the first year of teaching when teachers were in a new context (Hoy & Spero, 2005;Kulinna, Cothran, & Kloeppel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The review, along with other literature, emphasized that to increase self-efficacy and positively impact the rate at which teachers implement health concepts in classrooms, teachers' confidence in being able to teach health needs to be improved and supported. [73][74][75][76][77] De Buhr et al 37 identified that teachers often feel their own HL is not sufficient to teach children, despite HL being included in the curriculum they are required to teach (Table 3). This is concerning, as 38% (n = 11) of health interventions identified by this study required the teacher to take on the role of the HLM (Table 5).…”
Section: Knowledge and Confidence Of Educatorsmentioning
confidence: 99%
“…Therefore, professional development opportunities should be available to inservice classroom teachers to improve their teaching efficacy in PE. Kulinna, Cothran, and Kloeppel (2011) showed that classroom teachers' self-efficacy in teaching healthy behavior content increased after participating in workshops. Third, some classroom teachers lack the confidence to teach key areas of the PE curriculum (Morgan & Hansen, 2007).…”
Section: Introductionmentioning
confidence: 99%